2021
DOI: 10.1002/alz.12377
|View full text |Cite
|
Sign up to set email alerts
|

Tau pathologies mediate the association of blood pressure with cognitive impairment in adults without dementia: The CABLE study

Abstract: Introduction:This study delineated the interrelationships among blood pressure (BP), cerebrospinal fluid (CSF) core biomarkers of Alzheimer's disease (AD), and cognition. Methods:The linear regression analyses were conducted in 1546 non-demented participants (mean age of 61.58 years, range 40 to 89 years; 40% female; average days of BP measurement, 9.10 days). Mediation analyses with 10,000 bootstrapped iterations were used to explore the mediation effects.Results: A clear age-related pattern of BP was delinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
30
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 44 publications
3
30
3
Order By: Relevance
“…One prior study failed to detect any relationship between BPV and cerebral spinal fluid tau levels. 20 It is unclear why the present study found a different pattern of results, but it could be that cerebral spinal fluid tau levels are less sensitive to regional tau deposition within specific brain areas affected in the earliest stages of AD (eg, the entorhinal cortex) where robust relationships between BPV and tau were observed. This particular study examined day-to-day BPV over an average of 9.1 days, 20 suggesting mechanisms underlying BPV may differ by timespan of BP measurement.…”
Section: Discussioncontrasting
confidence: 70%
See 4 more Smart Citations
“…One prior study failed to detect any relationship between BPV and cerebral spinal fluid tau levels. 20 It is unclear why the present study found a different pattern of results, but it could be that cerebral spinal fluid tau levels are less sensitive to regional tau deposition within specific brain areas affected in the earliest stages of AD (eg, the entorhinal cortex) where robust relationships between BPV and tau were observed. This particular study examined day-to-day BPV over an average of 9.1 days, 20 suggesting mechanisms underlying BPV may differ by timespan of BP measurement.…”
Section: Discussioncontrasting
confidence: 70%
“…20 It is unclear why the present study found a different pattern of results, but it could be that cerebral spinal fluid tau levels are less sensitive to regional tau deposition within specific brain areas affected in the earliest stages of AD (eg, the entorhinal cortex) where robust relationships between BPV and tau were observed. This particular study examined day-to-day BPV over an average of 9.1 days, 20 suggesting mechanisms underlying BPV may differ by timespan of BP measurement. 22 The findings of the present study could suggest vascular dysfunction represented by increased BPV contributes to pathological tau accumulation; however, replication of the present study finding is needed to further support a role for increased BPV in cerebral tau changes.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations